CONTRIBUTIONS BY NON GOVERNMENTAL ORGANISATIONS TOWARDS POVERTY ALLEVIATION IN ZIMBABWE - Damiyano, David; Dorasamy, Nirmala (International Journal of Psychosocial Rehabilitation, 2020)
This research empirically examined the contributions that are being made by non-governmental organizations to reduce poverty in Zimbabwe. Annual time-series data was used; certain variables, which include foreign aid, unemployment, inflation, and literacy rate, were regressed directly on poverty using E-views 7 software in trying to come up with the best result on the impact of NGOs in Zimbabwe. Certain relationships were discovered, and foreign aid by NGOs had a positive relationship, indicating something needs to be done for us as Zimbabweans to fully benefit from the aid. The study revealed that the NGOs that were operating in Zimbabwe have performed reasonably well besides the challenges they were facing in trying to attain their objectives. Food aid is the most significant contribution done by these NGOs. The study recommended that to make a long-term and significant contribution to poverty reduction, NGOs should extend the length of their funding contracts. The study also recommended that the government should attract foreign direct investment in any possible way through ensuring a steady political and economic environment so as for the economy to create job opportunities, therefore, reducing the unemployment rate and poverty at the end as people will have money in their pockets.